2015
DOI: 10.5194/angeo-33-1147-2015
|View full text |Cite
|
Sign up to set email alerts
|

In situ evidence of breaking the ion frozen-in condition via the non-gyrotropic pressure effect in magnetic reconnection

Abstract: For magnetic reconnection to proceed, the frozen-in condition for both ion fluid and electron fluid in a localized diffusion region must be violated by inertial effects, thermal pressure effects, or inter-species collisions. It has been unclear which underlying effects unfreeze ion fluid in the diffusion region. By analyzing in-situ THEMIS spacecraft measurements at the dayside magnetopause, we present clear evidence that the off-diagonal components of the ion pressure tensor is mainly responsible for breaking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…The appearance of the two distinct cold and hot populations of ions leading to a non‐Maxwellian distribution suggests that these observations have taken place where ions were demagnetized [e.g., Dai et al , ; Zhou et al , ]. This idea is supported by the nongyrotropic shape of the ion distributions in VDF plots (Figures g and h), where an asymmetric reconnection [e.g., Lee et al , ] can lead to mixing up distinct sources of plasma with different energies.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…The appearance of the two distinct cold and hot populations of ions leading to a non‐Maxwellian distribution suggests that these observations have taken place where ions were demagnetized [e.g., Dai et al , ; Zhou et al , ]. This idea is supported by the nongyrotropic shape of the ion distributions in VDF plots (Figures g and h), where an asymmetric reconnection [e.g., Lee et al , ] can lead to mixing up distinct sources of plasma with different energies.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…The normal electric field E N was mainly balanced by −V e × B, that is, E N was mainly the Hall electric field J × B/n e e = V i × B − V e × B ~ −V e × B given that quasi‐neutrality (n i ≈ n e ) was satisfied. From the perspective of the ion momentum equation, the Hall electric field was mainly balanced by ion pressure gradient term (Dai et al, , ; Zhang et al, ). Note that there was a positive E N peak adjacent to the negative E N above the neutral sheet.…”
Section: Observations Of the Idrmentioning
confidence: 99%
“…The ion velocity distributions in V M ‐V N plane (perpendicular to the magnetic field) around the two separatrices exhibit nongyrotropy, which is more evident in Figure c that the phase space densities on the upper right and lower left quadrants are larger than that in the two other quadrants. The nongyrotropic ion distributions were likely the consequence of the mixture of incoming ions and already accelerated ions (Dai et al, ). We can safely conclude that MMS crossed an IDR of this X line based on the evidence of Hall electromagnetic fields, Hall current, and the demagnetized ions.…”
Section: Observations Of the Idrmentioning
confidence: 99%
“…UT near the neutral sheet (Figure 1a and 1b). Such reversal in B z and v x is the signal as the spacecraft crossing a tailward retreating X-line (Dai et al, 2011(Dai et al, , 2015Hones, 1976;Zhang et al, 2010Zhang et al, , 2015, as shown in the schematic in Figure 1i. From 2154 to 2157 UT, MMS observes typical tenuous plasma sheet ions and electrons from 1 to 20 keV (panels e and f).…”
Section: Observations and Analysismentioning
confidence: 97%